Isolation and Number of Gonadal Primordial Germ Cells (Gonadal PGCs) on the Stages of Early Embryonic Development of KUB Chicken - Soni Sopiyana; M. A. Setiadi; M. Fahrudin; I. Supriatna (Faculty of Animal Science, Bogor Agricultural University, 2017)
Primordial germ cells (PGCs) are cells that will differentiate themselves into spermatogonia in the testis or oogonia in the ovary. Primordial germ cells arise from epiblast and circulate through the bloodstream and finally entering gonadal anlage. The aim of this study was to determine the number of gonadal PGCs of KUB chicken at different development stages. Sixty KUB chicken fertile eggs were divided into four groups (6, 7, 8, and 9 days incubation periods), and incubated at 38 oC with a humidity of 60%. Harvesting was synchronized to the embryonic development at 6-9 d. Gonads were collected using sharp tweezers, and were placed in Eppendorf tube 1.5 mL containing 500 µL PBS [-]. Gonadal PGCs were purified using PBS [-]. The results showed that the average number of gonadal PGCs at 6, 7, 8, and 9 d were 113.7; 143.5; 92.9; and 85.7 cells per embryo, respectively. Number of gonadal PGCs per embryo of KUB chicken were significantly affected by stage of embryonic development (P<0.05), which reached a peak at day 7 of incubation, so that the isolation and collection of PGCs from the gonads were recommended at day 7 of incubation. This information is useful in production of germline chimera of other Indonesian local chickens.